Dynamic Capital Structure as Strategic Leverage: Evidence from Garuda Indonesia - Oey Richard Arthur Wijaya; Arief Wibisono Lubis (Owner : Riset dan Jurnal Akuntansi, 2026)
The core problem is whether Garuda’s failure to adjust in a timely manner became a strategic disadvantage that intensified avoidable distress. This study addresses gaps in research on SOE adjustment behaviour, leverage dynamics in aviation, and the economic cost of delayed rebalancing, framing capital structure as a strategic capability rather than a static ratio. This study uses a mixed-method design focused on Garuda Indonesia, benchmarked against nine airlines (2015-2024) through a multiple-case comparative panel. . The primary method is System GMM, used to estimate the Speed of Adjustment (SOA) and identify dynamic leverage behaviour, complemented by Random Effects estimation of leverage determinants and Monte Carlo simulation (?10,000 paths) to assess resilience outcomes.  Profitability negatively affects leverage (? = ?1.05; p < 0.01), while tangibility positively influences it (? = +0.62; p < 0.01), consistent with pecking order and trade-off theories. The System GMM estimation across ten airlines shows a significant lagged-leverage coefficient (? = 0.316; p < 0.01), implying a Speed of Adjustment (SOA) of 0.684, compared to a firm-level testing of Garuda that shows ? = 0.7493 or SOA of 0.257, and  actual cost of capital during distress that was 6.7x higher than it would have been under a balanced capital structure. After homologation, leverage persistence turned negative (? = -0.1464; SOA = 1.15), reflecting an overshooting phase consistent with rapid deleveraging, restored managerial discretion, and materially reduced adjustment frictions. These results verify that homologation substantially improved policy effectiveness. Monte Carlo simulations (10,000 paths) reveal a sharp improvement in resilience: Garuda’s mean DSCR rose from -1.56 pre-homologation (2015-2021) to +0.72 post-homologation (2022-2024), demonstrating reduced tail risk and a structural recovery in solvency without changes in operational volatility. The study contributes to capital structure theory by demonstrating that dynamic adjustment speed itself is a strategic variable, particularly under financial distress.